2022
DOI: 10.1038/s41562-022-01355-1
|View full text |Cite
|
Sign up to set email alerts
|

Rapid learning of a phonemic discrimination in the first hours of life

Abstract: Human neonates can discriminate phonemes, but the neural mechanism underlying this ability is poorly understood. Here we show that the neonatal brain can learn to discriminate natural vowels from backward vowels, a contrast unlikely to have been learnt in the womb. Using functional near-infrared spectroscopy, we examined the neuroplastic changes caused by 5 h of postnatal exposure to random sequences of natural and reversed (backward) vowels (T1), and again 2 h later (T2). Neonates in the experimental group we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 93 publications
0
16
0
Order By: Relevance
“…If the acoustic filter of the womb is the only constraint on learning, fetuses should be able to exploit their prenatal exposure to segmentation cues. But this is not the case: Although newborns show phonemic perceptual learning for individually presented vowels (Wu et al, 2022), they do not yet show the ability to segment fast speech sounds from continuous speech (Bijeljac-Babic et al, 1993), indicating a maturational rather than environmental constraint on the processing of fast modulations in speech, as this information was already available in utero.…”
Section: Early Low-pass Filtering Of Speech: the Womb Versus The Brainmentioning
confidence: 99%
“…If the acoustic filter of the womb is the only constraint on learning, fetuses should be able to exploit their prenatal exposure to segmentation cues. But this is not the case: Although newborns show phonemic perceptual learning for individually presented vowels (Wu et al, 2022), they do not yet show the ability to segment fast speech sounds from continuous speech (Bijeljac-Babic et al, 1993), indicating a maturational rather than environmental constraint on the processing of fast modulations in speech, as this information was already available in utero.…”
Section: Early Low-pass Filtering Of Speech: the Womb Versus The Brainmentioning
confidence: 99%
“…It is not surprising that reading/writing is built on spoken language as by the time children are introduced to literacy skills they have already mastered the spoken language to a large extent. Modern research suggests that newborn infants develop initial language-related skills shortly after birth (Wu et al, 2022). Eye movement studies also suggest that eye movements during text reading align with the rate of speech production (Gagl et al, 2022).…”
mentioning
confidence: 99%
“…Additionally, the inclusion of non-speech emotional materials may offer insights into the potential right lateralization of emotional processing in the neonatal brain. While prior studies (including some cited herein) have identified right lateralization for emotional processing in full-term neonates (Cheng et al, 2012; Zhang et al, 2019;see Bisiacchi & Cainelli, 2022 for a comprehensive review), the introduction of non-speech materials can help disentangle the confounding effects of left lateralization, which is associated with language processing and has been identified in both preterm (Mahmoudzadeh et al, 2013) and full-term neonates (Kotilahti et al, 2010; May et al, 2018; Peña et al, 2003; Sato et al, 2012; Vannasing et al, 2016; Wu et al, 2022).…”
Section: Discussionmentioning
confidence: 98%